Late Presentation of Partial Atrioventricular Septal Defect: A Case Report - Ghada Kareem; Wadhah Mahbuba (مجلة الكوفة الطبية, 2022)
Atrioventricular septal defect is a spectrum of congenital heart defects that can be classified as either complete or partial with the complete form being the most common and usually present in the neonatal period with congestive heart failure. However, partial defects can remain asymptomatic and present later in adulthood with variable degrees of heart failure. The case under investigation is a middle aged female with a 2-year history of worsening dyspnea and recurrent chest infections due to undiagnosed partial atrioventricular septal defects. As a conclusion, it is important to establish a screening program to detect the asymptomatic cases early and prevent delay consequences.